Using “Memes” as a Marketing Communication Tool in Connecting with Consumers within the Age of Digital Connectivity - Vasile, Sorina; Mototo, Lebogang; Chuchu, Tinashe (International Review of Management and Marketing, 2021)
The modern globalisation and the expansion of multinational brands and social communications has resulted in the youth-consumer market of today being relentlessly exposed to increasing competitive multimedia messages and advertising. This research explored the impact of brand attitude, brand perception and social influence on brand engagement. It also investigated the impact of brand engagement on behavioural intention. The data was collected through a sample of 350 questionnaires administered to a target population consisting of young consumers in Braamfontein, Johannesburg. The results indicated that Brand Perception and Social Influence both have a positive and significant effect on brand engagement. That is, while Brand Attitude positively influences Brand Engagement, the effect was not found to be significant. Brand Engagement, the mediator variable was strongly supported and had a highly significant effect on Behavioural Intention. Managerial implications, limitations, and further research directions. Keywords: Memetic marketing, advertising, behavioural intention, JEL Classifications: M3, M30, M31 DOI: https://doi.org/10.32479/irmm.11313